Self-employment of rural-to-urban migrants in China - Corrado Giulietti; Guangjie Ning; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2011)
This paper focuses on the determinants of self-employment among rural to urban migrants in China. Two self-selection mechanisms are analysed: the first relates to the manner in which migrants choose self-employment or paid work based on the potential gains from either type of employment; the second takes into account that the determinants of the migration decision can be correlated with employment choices. Using data from the 2008 Rural-Urban Migration in China and Indonesia (RUMiCI) survey, a selection model with endogenous switching is estimated. Earnings estimates are then used to derive the wage differential, which in turn is used to model the employment choice. The procedure is extended to account for migration selectivity and to compare individuals with different migration background and employment histories. The results indicate that self-employed individuals are positively selected with respect to their unobserved characteristics. Furthermore, the wage differential is found to be an important driver of the self-employment choice.
urn:nbn:de:101:1-20110629911
Keywords: J23; J61; O15; 330; self-employment; wages; rural to urban migration; selection bias magnets; European Union